How to say it! choice words, phrases, sentences, and paragraphs for every situation - Maggio, Rosalie (Prentice Hall, 1990)
Contains advice on writing effective business and social letters in forty subject areas, with lists of words, phrases, sentences, and paragraphs relevant to each topic, and sample letters that may be reproduced and modified for individualized use.